2020
DOI: 10.1007/s13762-020-03029-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a magnetic activated carbon adsorbent for the removal of common pharmaceuticals in wastewater treatment

Abstract: This work aims to study the use of a powdered activated carbon with magnetic properties as adsorbent to remove common pharmaceuticals in wastewater treatment. This hybrid material was prepared from powdered activated carbon that was combined with iron oxide nanoparticles and was characterized by infrared spectroscopy and X-ray diffractometry. It was also assessed for its adsorption ability using ibuprofen and amoxicillin as model drugs. Under the tested conditions, adsorption equilibrium was reached at 160 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Additionally, the authors also observed that there were no significant differences in COD removal after filtration and magnetic separation for both adsorbents with incorporated iron oxide nanoparticles. Vargues et al [232] used PAC and PAC combined with iron oxide nanoparticles (PACMAG) as adsorbents to remove common pharmaceuticals (ibuprofen and amoxicillin). These authors observed that the kinetic models and the isothermal models were different between PAC and PACMAG for both drugs, which means that the incorporation of iron oxide nanoparticles can influence the adsorption mechanism.…”
Section: Main Challenges and Recent Advancesmentioning
confidence: 99%
“…Additionally, the authors also observed that there were no significant differences in COD removal after filtration and magnetic separation for both adsorbents with incorporated iron oxide nanoparticles. Vargues et al [232] used PAC and PAC combined with iron oxide nanoparticles (PACMAG) as adsorbents to remove common pharmaceuticals (ibuprofen and amoxicillin). These authors observed that the kinetic models and the isothermal models were different between PAC and PACMAG for both drugs, which means that the incorporation of iron oxide nanoparticles can influence the adsorption mechanism.…”
Section: Main Challenges and Recent Advancesmentioning
confidence: 99%
“…where, C 0 is the initial adsorbent concentration in solution (mg/L), V is the solution volume (L), m is the weight of adsorbent used per liter of solution (g/L), q t (mg/g) is the amount of adsorbent retained at time t, and α (<1) and k 0 are constants. The Bangham model was tested to adsorb pharmaceutical compounds [35,36].…”
Section: Introductionmentioning
confidence: 99%